2017
DOI: 10.1177/1756287217738150
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic comparison of subcutaneousversusintramuscular leuprolide acetate formulations in male subjects

Abstract: Both formulations demonstrated consistent delivery of drug over 1 month; however, SC-LA provided a longer duration of action than expected based on the dosing interval. This profile suggests that SC-LA will provide effective suppression of T over a longer period of time, permitting greater injection scheduling flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…Although direct statistical comparisons of PK parameters were not conducted as the populations were different in each trial, the overall PK profiles from each study (“Bilaterally orchiectomized male study,” pivotal trials, and “PKPD study”) were comparable. The observation for serum LA level in bilaterally orchiectomized males is consistent with the Gel‐LA clinical study in healthy subjects (“PKPD study”), where duration of measurable and adequate serum LA levels similarly ranged from 42‐56 days after dosing (Table 2, Figure 2B), exceeding the 1‐month dosing period 21 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although direct statistical comparisons of PK parameters were not conducted as the populations were different in each trial, the overall PK profiles from each study (“Bilaterally orchiectomized male study,” pivotal trials, and “PKPD study”) were comparable. The observation for serum LA level in bilaterally orchiectomized males is consistent with the Gel‐LA clinical study in healthy subjects (“PKPD study”), where duration of measurable and adequate serum LA levels similarly ranged from 42‐56 days after dosing (Table 2, Figure 2B), exceeding the 1‐month dosing period 21 …”
Section: Discussionsupporting
confidence: 83%
“…In pivotal trials, clinical efficacy of the four doses of Gel‐LA demonstrated continuous suppression of T to concentrations ≤20 ng/dL through achievement of median serum levels of LA above 0.05 ng/mL (assay lower limit of quantification [LLOQ]: 0.1 ng/mL for 1‐ and 3‐month and 0.05 ng/mL for 4‐ and 6‐month formulations) 16‐20 . The pharmacokinetics (PK) of a single dose of Gel‐LA have also previously been described in healthy subjects (“PKPD study”) 21 …”
Section: Introductionmentioning
confidence: 98%
“…In a phase 1 study of 1-month doses of IM-LA and SC-LA, serum LA levels in the SC-LA arm remained above the limit of quantitation (defined as effective) for 10−20 days longer than IM-LA. These PK differences resulted in very different PD profiles, with SC-LA suppressing LH and maintaining median T levels at castrate level for a longer period (at least 56 days vs. 35 days in SC-LA and IM-LA arms, respectively) [37]. These outcomes are likely attributed to differences in the controlled-release technologies and the data challenge the commonly accepted position that ADT therapies are interchangeable.…”
Section: Current Armamentarium Of Drugs Targeting Reduction In Testosmentioning
confidence: 99%
“…Prostate cancer, the second most common type of cancer in men (14%), is the main cause of death among cancer patients and is the sixth cause of cancer‐related death (6%) worldwide . Suppression of the serum testosterone to concentrations below the castration levels (<50 ng/dL) is the standard palliative treatment method in patients with advanced prostate cancer . Leuprolide acetate (LA) and triptorelin acetate (TA) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC methods and quantification by radioimmunoassay and MS/MS detections are analytical methods, which have been developed for quantification and pharmacokinetic study of LA. Moreover, quantification of TA has been developed by LC–MS/MS .…”
Section: Introductionmentioning
confidence: 99%